2019
DOI: 10.1029/2019ja026820
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Ray Flashes Produced by Lightning Observed at Ground Level by TETRA‐II

Abstract: In its first 2 years of operation, the ground-based Terrestrial gamma ray flash and Energetic Thunderstorm Rooftop Array (TETRA)-II array of gamma ray detectors has recorded 22 bursts of gamma rays of millisecond-scale duration associated with lightning. In this study, we present the TETRA-II observations detected at the three TETRA-II ground-level sites in Louisiana, Puerto Rico, and Panama together with the simultaneous radio frequency signals from the lightning data sets VAISALA Global Lightning Dataset, VA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…For the first question, previous studies have reported downward TGFs observed at the ground level associated with both natural and triggered CGs. In natural CG cases, downward gamma rays have been linked with downward stepping negative leaders (Abbasi et al, 2018; Pleshinger et al, 2019) but this type of X‐ray/gamma ray generation from leader steps is at least 2 to 4 orders of magnitude weaker in fluence than satellite‐observed TGFs and appears to be a distinct phenomenon.…”
Section: Measurements and Analysismentioning
confidence: 99%
“…For the first question, previous studies have reported downward TGFs observed at the ground level associated with both natural and triggered CGs. In natural CG cases, downward gamma rays have been linked with downward stepping negative leaders (Abbasi et al, 2018; Pleshinger et al, 2019) but this type of X‐ray/gamma ray generation from leader steps is at least 2 to 4 orders of magnitude weaker in fluence than satellite‐observed TGFs and appears to be a distinct phenomenon.…”
Section: Measurements and Analysismentioning
confidence: 99%
“…Therefore, the cases of Abbasi et al (2018) are still 10 −6 to 10 −4 times smaller than the present case. The ground-based experiment TETRA-I/II also reported 46 downward TGFs in total during summer as well (Pleshinger et al, 2019;Ringuette et al, 2013). Gamma-ray counts of TETRA-II BGO (25.4 × 2.5 × 2.5 cm 3 ) range from 19 to 203.…”
Section: Comparison With Other Tgf Observationsmentioning
confidence: 99%
“…In addition to satellite observations, TGFs have been observed by on-ground apparatus (Abbasi et al, 2018;Bowers et al, 2017;Dwyer et al, 2004Dwyer et al, , 2012Hare et al, 2016;Pleshinger et al, 2019;Ringuette et al, 2013;Tran et al, 2015;Wada et al, 2020). Observations of Bowers et al (2017), , , and (Wada et al, 2020) were performed in winter thunderstorms, and the others in summer ones.…”
Section: Comparison With Other Tgf Observationsmentioning
confidence: 99%
“…Recent observations have shown that gamma radiation correlates with radio-frequency radiation and is generated at the last stage of lightning leader channel development prior to the lightning return stroke [14]. The bursts of 30-80 MHz radiation because of leader stepping were observed in [15].…”
Section: Introductionmentioning
confidence: 99%